Application Study on Active Advanced Support Technology in Deep Roadway under Mine Goaf. (24th November 2020) - Jiang, Pengfei; Xiao, Peng; Meng, Fanbao; Jing, Suolin; Zhang, Jingkai; Wang, Ge; Zhao, Peng
Abstract : To solve the problems of the rapid advance of the working face was delayed by complicated working procedure and high labor intensity, and the severe damage of roof bolt (anchor cable) induced by advanced hydraulic support, the deformation characteristics of surrounding rock, and the supporting principle of grouting truss anchor cable were analyzed theoretically by taking the roadway of 3_(down) coal seams 2326# working face in Sanhekou coal mine as the research object; then, the mechanical model of supporting structure of roadway under goaf was established. Based on this model, the optimal supporting scheme was determined, and the active advanced support technology scheme of "advanced grouting truss anchor cable" was proposed to take the place of the existing single pillar. The deformation and failure characteristics of surrounding rock of the working face leading roadway were observed and analyzed on-site. Within the allowable range of reading error, the results showed that the maximum displacement of medium-deep base point and shallow base point of two roadways was 15.2 cm and 10.9 cm, respectively; the pressure value had a more obvious jump increase when the distance between each measuring point and the working face was about 35 m, which means the range is strongly affected by the advance mining, and the area affected by advanced mining was 35 m ahead of the working face. It was observed that the lowest position of roof separation development ranged from 0.71 m to 2.73 m. The separation layer was generally distributed in the range of 0.73 m-2.49 m, and the fracture area was roughly distributed in the range of 0.01 m-0.62 m. Under the condition of overlying goaf, there was a complete stress structure, which can meet the requirements of suspension support.